A complementary perspective on legitimation in regional development: the crisis of acceptance of liquefied natural gas (LNG) on the touristic island of Rügen - Buika, Ihar; Schiller, Daniel (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
As the substance of public interest in spatial planning and development remains permanently challenged, the relationship between legitimacy and acceptance is constantly in the focus of discussion. After the wave of interest in participation-intensive communicative legitimation approaches from the 1970s, a still new generation of agonistic approaches has been intensively discussed since the 2000s, raising expectations of a more efficient resolution of conflicts which continue to pose a risk of disturbing or preventing deliberative negotiation. Although such approaches are participation-oriented, too, there are nevertheless concerns that these expectations could remain unfulfilled like those regarding the communicative approach nowadays are. Against this background, our qualitative study, based on 20 semi-structured interviews, is intended to enrich discussion about the complementary perspective on legitimation by clarifying aspects that condition the composition of rational, communicative and agonistic legitimation approaches in particular development projects. The protest against the liquefied natural gas terminal on the island Rügen demonstrates that strong recourse to the rational legitimation approach has restricted participation and thus overshadowed communicative and agonistic demands for broader local participation and led to a severe crisis of acceptance. We argue that it is essential in terms of acceptance-fostering to counter complex issues with equally complex solutions. Moreover, effective and accepted planning and development policy depends on a spatially and temporally sensible, pragmatic composition of legitimation approaches.